Cascading failures modeling of electronic circuits with degradation using impedance network. (May 2023) - Jin, Yi; Zhang, Qingyuan; Chen, Yunxia; Lu, Zhendan; Zu, Tianpei
Abstract: Due to the complex structural and functional coupling of electronic circuit systems, cascading failures have gradually become a significant threat for their reliability. Though several attempts have been made to predict the cascading failure behavior of circuit systems through network-based models incorporating the physical laws of circuits, these methods can only characterize the cascading failures triggered by sudden failure modes without considering the correlation effects caused by the pervasive degradation of components. To handle this problem, in this paper, the impedance network is used as a prototypical model and a novel current redistribution factor considering component degradation is proposed. Based on this, two types of cascading failure propagation processes, namely the slow propagation accompanied with continuous degradation and the fast propagation due to the degradation-triggered failure, are quantitatively described, with which a simulation framework for the cascading failure is developed. A case study is presented to illustrate the proposed models and to analyze the reliability of a typical electronic circuit system. The proposed model is also validated by comparing the obtained results with those generated from the SPICE software simulation. Highlights: Degradation affects the cascading failure of large-scale electronic circuits. A current redistribution factor describing the degradation impacts is derived. Failure propagations triggered by degradation and open-circuit are quantified. Degradation rate and temperatures influence the circuit cascading failure behavior. The errors of the predicted currents are less than 4 % .